Familial Mediterranean fever in Romania: a case report and literature review - Iuhas, Alin; Marinău, Cristian; Niulaș, Larisa; Futaki, Zsolt; Balmoș, Andreea; Kozma, Kinga; Indrieș, Mirela; Sava, Cristian (Frontiers in Pediatrics, 2025)
Familial Mediterranean Fever (FMF) is a hereditary autoinflammatory disease characterized by recurrent fever and systemic inflammation, most prevalent in Eastern Mediterranean populations. Rare in regions like Romania, FMF presents diagnostic challenges and risks severe complications if untreated. We report a 7-year-old Romanian girl, from a non-classical ethnic background, with recurrent febrile episodes and elevated inflammatory markers. Genetic testing confirmed a homozygous MEFV c.2082G>A (p.Met694Ile) variant. Colchicine therapy reduced flare frequency and normalized inflammatory markers. FMF should be considered in atypical populations with recurrent inflammation. Genetic testing aids diagnosis in non-endemic regions, enabling early colchicine treatment to prevent complications.